A free space optical interconnect based biosequence analysis system - Ao, Tao, author (Colorado State University. Libraries, 2003)
Free space optical interconnects (FSOI) are of considerable interest for their potential of parallel high bandwidth optical data links. In order to demonstrate the feasibility of applying FSOI technology in complex information processing systems, a prototype FSOI based biosequence analysis system was constructed and tested. This thesis reports the design, setup and testing of the FSOI based biosequence analysis system, which has 64 optical channels that feeds optical signal to a custom designed biosequence processor chip. The system implements the basic local alignment search tool (BLAST) algorithm using a biosequence processor chip and a programmable logic device. The biosequence processor chip has a 8x8 comparison array, in which each basic comparison unit has a built-in optical input. A diffractive optical elements multiplies a modulated laser beam into an 8 x 8 spot array and a projection lens relays the spot array onto the optical inputs of the biosequence processor chip. Four major system development tasks were achieved: 1. System algorithm and architecture design; 2. Development of a FSOI processor chip for the biosequence comparisons; 3. Optics system design and setup; 4. Functionality and reliability tests 5. Biosequence analysis. The FSOI biosequence analysis system successfully analyzed homologous and inhomologous biosequences. The performance of the proof of principle system is compared with present electronic system. The potential of the FSOI system concept is also investigated.
Keywords: electrical engineering